2005
DOI: 10.1016/j.cub.2005.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Blinking Suppresses the Neural Response to Unchanging Retinal Stimulation

Abstract: Blinks profoundly interrupt visual input but are rarely noticed, perhaps because of blink suppression, a visual-sensitivity loss that begins immediately prior to blink onset. Blink suppression is thought to result from an extra-retinal signal that is associated with the blink motor command and may act to attenuate the sensory consequences of the motor action. However, the neural mechanisms underlying this phenomenon remain unclear. They are challenging to study because any brain-activity changes resulting from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 27 publications
7
101
1
Order By: Relevance
“…3), i.e. the region where based on previous functional imaging results (Bodis-Wollner et al, 1999;Bristow et al, 2005) blink-related brain response might have been expected (see Discussion).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…3), i.e. the region where based on previous functional imaging results (Bodis-Wollner et al, 1999;Bristow et al, 2005) blink-related brain response might have been expected (see Discussion).…”
Section: Resultsmentioning
confidence: 64%
“…We, therefore, conclude that these fronto-anterior ECoG potentials reflect ocular blink artifacts that extend to the intracranial space through mechanisms of electrical volume conduction. This conclusion is supported by the fact that previous neuroimaging studies on the neuronal basis of blinking lend little support for the assumption that the anterior prefrontal region is a major site of blink-related brain activation (Bodis-Wollner et al, 1999;Bristow et al, 2005;Kato and Miyauchi, 2003;Tsubota et al, 1999;van Eimeren et al, 2001 For each electrode position, the Z-score of the blink related artifact at the time point of the artifact peak (see Material and methods for further details) is given. Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, a recent study by Smilek, Carriere, and Cheyne (2010) showed that mindless reading is associated with increased blinking. This result could help explain the deficit in encoding the lexical features of words, since frequent blinking is associated with deactivation of cortical areas that process the external visual world (Bristow, Haynes, Sylvester, Frith, & Rees, 2005). Consistent with these findings are results indicating that reading comprehension can be compromised when critical regions of the text are poorly encoded (Christianson, Williams, Zacks, & Ferreira, 2006;Sanford & Graesser, 2006;Stine-Morrow, Noh, & Shake, 2010).…”
mentioning
confidence: 56%
“…In most studies that reported activation of the visual cortex accompanying saccades in total darkness, subjects were required to keep their eyes open. On the contrary, our subjects were required to keep their eyes closed in order to avoid misinformed activation by blink (Kato and Miyauchi 2003;Bristow et al 2005) and to equalize the physical condition of the eyes between the saccade experiment and REM sleep experiment. Therefore, saccades with closed eyes might underlie the lack of activation in the visual cortex in the present experiment.…”
Section: Activation Preceding Remmentioning
confidence: 99%